Nonalpine Thyroid Angiosarcoma in a Patient with Hashimoto Thyroiditis - Nadia Innaro; Elena Succurro; Giuseppe Tomaino; Franco Arturi (Case Reports in Oncological Medicine)
Thyroid angiosarcoma is an uncommon thyroid carcinoma and its incidence is the highest in the European Alpine regions. Thyroid angiosarcoma is also a very aggressive tumor that can rapidly spread to the cervical lymph nodes, lungs, and brain or can metastasize to the duodenum, small boewl, and large bowel. Although it is histologically well defined, clear-cut separation between the angiosarcoma and anaplastic thyroid carcinoma is difficult. A 49-year-old Caucasian female patient, born and resident in Southern Italy (Calabria), in an iodine-sufficient area, was admitted to the Surgery Department because she presented with a painless mass in the anterior region of neck enlarged rapidly in the last three months. After total thyroidectomy and right cervical lymphadenectomy, postoperative histological examination revealed the presence of a thyroid angiosarcoma with positive staining for CD31 and for both Factor VIII-related antigen and Vimentin and only partially positive for staining pancytokeratin and presence of metastasis in cervical, supraclavicular, mediastinal and paratracheal lymph nodes. The patient started adjuvant chemotherapy and she was treated for 6 cycles with Doxorubicin, Dacarbazine, Ifosfamide, and Mesna (MAID). After 22 months from surgery, the patient is still alive without both local and systemic recurrence of the disease.